HUBUNGAN KESENJANGAN ANTARA KENYATAAN DAN HARAPAN BUDAYA ORGANISASI DENGAN KINERJA PEGAWAI DI LAN PERWAKILAN JAWA BARAT JAWA BARAT - Teni Listiani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
This research aims at finding out the corelation between the gap of current practices and ideals of organizational culture and employees’s performance in institution National Institute of Public Administration West Java Regional Office. This study employs an explanatory survey method, which is commonly used to correlate and examine two variables. In this resarch an independent variable (X) is the gap between the current practices and ideals of organizational culture asperceived by employees, whereas a dependent variable (Y) is employees’s performance. The result of hypothesis examination shows that at the level of 0.0, there is a correlation between the gap of current practices and ideals of organizational culture and employees’s performance with the degree of correlation categorized as strong (rs = -0.643) The conclusion of this study shows that employees: a) perceive the current practices of organizational culture are oreiented towards power and role culture. b) employees expect thatorganizational culture should be oriented toward achievements and support culture. Another connclusion is that the correlation between current practices of organizational culture and employees’s performance is negative, and the correlation between ideals oforganizational culture and employees’s performance is negative as well.